Short run and long run Ricardian equivalence: an evidence from Malaysia - Abd Rahman, Muhammad Daaniyall; Law, Siong Hook; Mohd Noor, Zaleha (Universiti Putra Malaysia Press, 2013)
This paper aims to test the validity of Ricardian equivalence in Malaysian economy with respect to the behavior of government debt and government spending on private consumption. To conduct the test, we choose Giorgioni and Holden (2003) model based on Bernheim (1987) model modifications. Auto-Regressive Distributed Lags (ARDL) Bounds test approach is employed to estimate the model in order to capture the hypothesis existence both in short run and long run. Consequently, the results show that the existence of Ricardian equivalence hypothesis is statistically rejected both cases. It also shows that Malaysians perceive government debt as net wealth and the government spending itself gives complementarity effect on private consumption. Therefore, Malaysian fiscal policy is a good macroeconomic stabilization tool to foster incessant economic growth.